Cold-induced urticaria in children: A multicenter, retrospective cohort study - Citlak, Hilal Karabag; Azkur, Dilek; Yildiz, Yuksel Kavas; Demirel, Ali Can; Kot, Hakan; Vezir, Emine; Orhan, Fazil (Ocean Side Publications Inc, 2023)
Background: Studies of cold-induced urticaria (ColdU) in pediatric patients are limited and not well characterized. Objective: The objective of the study was to investigate the characteristics of ColdU in children. Methods: A multicenter, retrospective chart review was performed in children ages <= 18 years diagnosed with ColdU at 11 pediatric allergy and immunology centers in Turkey between September 1, 2010, and August 31, 2022. Results: A total of 83 children with ColdU were included, 54.2% were girls, and the mean age of symptom onset was 8.8 years. The median duration of ColdU at the time of diagnosis was significantly higher in the girls than in the boys (1.0 years [0.0-13.8 years] versus 0.3 years [0.0-15.0 years]; p = 0.007). All the patients underwent an ice cube test, and 71.1% were found positive (typical ColdU). The mean +/- standard deviation age of onset was significantly higher in the patients with typical ColdU versus atypical patients (9.4 +/- 4.5 years versus 7.3 +/- 4.5 years; p = 0.041). Swimming alone and in combination with the wind were significantly the most reported triggers in patients with cold-induced anaphylaxis (ColdA) when compared with patients with ColdU and with nonanaphylactic symptoms (70.0% versus 28.9% [p = 0.022], and 50.0% versus 4.1% [p < 0.001], respectively). Only patients with other chronic urticaria were found to be associated with the development of typical ColdU (p = 0.036). The median total serum immunoglobulin E (IgE) was significantly higher in typical ColdU than in atypical patients (72.5 IU/mL [3.86 - 2500 IU/mL] versus 30.0 IU/mL [0.83 - 1215 IU/mL]; p = 0.007); however, total serum IgE differences were not found to affect ColdU resolution between the two groups (p = 0.204). The resolution was documented in 30.4%. Conclusion: Those who were boys and had a positive ice cube test result could have an association with earlier onset of ColdU. Those swimming alone on a windy day were at highest risk for ColdA. It is still unclear what characteristics are associated with the resolution of ColdU, and this warrants further investigation.
Keywords: Clinical-Features; Disease Course